The devil and demonism in early modern England - Johnstone, Nathan (Cambridge University, 2013)
Nathan Johnstone examines the concept of the Devil in English culture between the Reformation and the English Civil War. The author looks at the ways in which beliefs about the nature of the Devil changed as a consequence of the Reformation, and its impact on religious, literary and political culture.